EDUCATIONAL INTERVENTION AS AN INSTRUMENT FOR IMPROVING CARE GIVEN TO PATIENTS UNDER MECHANICAL VENTILATION IN AN INTENSIVE CARE UNIT NATAL/RN. (Fiep Bulletin - online, 2013)
Respiratory physical therapy on patients under mechanical ventilation (MV) is used to promote removal of secretions from the respiratory tract, easing gas exchanges. To that end, some actions guarantee the quality of assistance, such as the interruption of enteral nutrition before physical therapy maneuvers; sanitizing hands before and after physical therapy and the use of disinfected and/or sterile materials. Objectives: to observe the care given by the physical therapist before and after respiratory physical therapy as well as to identify whether there's a difference in assistance given to patients under MV by these professionals before and after an educational intervention. Methodology: quasi-experimental study, quantitative, timeseries outlining and prospective data, collected between November and December 2007 to March 2008, performed on a hospital in Natal, with 03 physical therapists. Results: we observed that before educational intervention on 94.9% of the situations, enteral nutrition was not interrupted before physical therapy maneuvers; after: 90.0% of the time, enteral nutrition was not interrupted (p= 0.57); before: on 58.7% of the observations hands were sanitized before respiratory physical therapy; after: on 53.3% of the observations hands were sanitized (p = 0.72); before: on 78.3% of the observed cases, after performing physical therapy, professionals sanitized their hands; after: on 73.3% of the observations, after performing physical therapy, professionals sanitized their hands (p = 0.69); before: on 69.9% of the observations, materials used during physical therapy were not disinfected or sterile; after: on 60.0% of the observations, these devices were disinfected or sterile (p = 0.04). Conclusion: there was no significant statistical difference after educational intervention on the interruption of enteral nutrition during physical therapy or regarding sanitizing of hands before and after the procedure. The only care which presented significant statistical difference was the use of disinfected and/or sterile materials in the group being studied.
Keywords: pneumonia; ventilator-associated; education; physical therapy department; hospital